2014
DOI: 10.4321/s0004-05922014000400005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of duration and level of feed restriction on performance and meat quality of broiler chickens

Abstract: Abdominal fat. Marshall broilers. Cost benefit. Feed:gain ratio. PALABRAS CLAVE ADICIONALESGrasa abdominal. Broilers Marshall. Coste/beneficio. Conversión alimenticia. SUMMARYTwo hundred and sixteen unsexed 14 daysold Marshall broiler chicks were used in a 3×3 factorial experimental design to test the effect of restricting feed intake of birds by 0 %, 20 % and 40 % levels for 2, 4 and 6 weeks after two weeks of the starter phase. The unrestricted (control) treatments were fed ad libitum throughout the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
9
8
0
Order By: Relevance
“…This result indicates that the loss in weight increased with increased duration of feed restriction. This agrees with Omosebi et al [18] who reported that live weight loss increased with the increased duration of feed withdrawal. In our experiment, group F which was fasted 8 days did not differ significantly from groups C and E. The probable explanation of this result is that birds of group F who were subjected to severe feed restriction tended to eat litter.…”
Section: Performance Of Male Broiler Chicks 32 To 40 Days Of Agesupporting
confidence: 92%
See 1 more Smart Citation
“…This result indicates that the loss in weight increased with increased duration of feed restriction. This agrees with Omosebi et al [18] who reported that live weight loss increased with the increased duration of feed withdrawal. In our experiment, group F which was fasted 8 days did not differ significantly from groups C and E. The probable explanation of this result is that birds of group F who were subjected to severe feed restriction tended to eat litter.…”
Section: Performance Of Male Broiler Chicks 32 To 40 Days Of Agesupporting
confidence: 92%
“…Feed restriction created a significant effect in the final live weight of experimental groups. Control group showed the highest value for final live weight (1808 ± 253 g) and group F that subjected to a longer period of feed removal showed the lowest value (1208 ± 124 g), which supports the statement that improvement in body weight of birds is highly correlated to feed consumption and duration of feed Restriction [9] [13]- [18]. During the same period carcass weight was significantly (P < 0.01) lower in restricted groups than that fed ad libitum.…”
Section: Performance Of Male Broiler Chicks 32 To 36 Days Of Agesupporting
confidence: 63%
“…In agreement with the present results, Hassanien (2011) reported that birds kept under higher levels of feed restriction consumed a little feed. Omosebi et al (2014) found that broiler reared under restriction (40 % for 6 weeks) had significantly reduced feed intake. Adeyemi et al (2015) reported that broiler chicks kept under feed restricted (80-75%) decreased daily feed intake.…”
Section: Resultsmentioning
confidence: 94%
“…Cristiano et al (2013) reported that increasing levels of feed restriction up to 40% reduced body weight gain on broiler chickens. In addition, Omosebi et al (2014) found that broiler chickens kept under feed restriction (40 % for 6 weeks) had superior feed gain ratio compared with the control group. Kouki and Bergaoui (2016) found that broilers chickens reared under restricted feeding from 35 to 49 days of age had significantly higher weight gain during the re-feeding period comparing to the control.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation